PENELITIAN PEMBERIAN TAMBAHAN PENGETAHUAN GIZI DAN KESEHATAN PADA MURID SEKOLAH DASAR - Anies Irawati; Trintrin Tjukarni; Dyah Santi Puspitasari (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1998)
Study on addition of the nutrition and health education conducted for elementary school children. The study conducted in 8 elementary school in Bogor, covered 252 school children (treatment group) and 269 school children (control group). Design of study is case control with pre and post test. The knowledge of nutrition and health consists: knowledge of the function of food and nutrition, food and nutrition resources, sanitary and health, other nutrition's knowledge such as food for pregnant women and lactating women, diarrhea and food for child development. The result of the study showed that after treatment (1-3 month), the knowledge for food and nutrition function increase from 47-50 percent becomes 70-83 percent. The knowledge for food and nutrition resources increase from 47-64 percent becomes 82-84 percent. The knowledge for sanitary and health increase from 50-78 percent becomes 85-91 percent. Other nutrition's knowledge increases from 45-66 percent becomes 68-84 percent. The best method is that teacher provides the material with special time (more than 90 percent student with true answer). Other methods, the teachers give material through ORKES topics (more than 80 percent with true answer). Base on the result of the study, the program to improve nutrition and health knowledge for elementary school children should be done. The program could be integrated with the curriculum.Keywords: nutrition knowledge, health knowledge, elementary school